Parameters determination for a linearly inhomogeneous half-space using characteristics of the time-harmonic surface waves. - Muravskii, Grigori
The paper presents a study of time harmonic surface waves in a linearly inhomogeneous half-space. The study is based on the solution of that problem for an arbitrary (from 0 to 1/2) value of Poisson's ratio. Vertical vibrations due to a vertical harmonic force, which at large distances from the force represent Rayleigh-type waves and transverse horizontal vibrations due to a horizontal force, which at large distances form waves of Love's type, are considered in detail. Material damping is taken into consideration. Inhomogeneity significantly affects relationships connecting wave characteristics and the frequency of vibration, and it is shown in the paper how this fact can be used for determining material properties (surface shear modulus, degree of inhomogeneity, damping ratio) with the help of experimental results concerning wave propagation over the surface of the half space. It is shown that for forced waves the relationship between the wave phase angle and distance can significantly differ from a straight line, i.e. the wave number varies with distance. Therefore, it is desirable to relate experimental and theoretical results to such parts of wave propagation line, which correspond to same phase angle intervals.
Keywords: Time-harmonic vibration; Inhomogeneous half-space.; Material damping; Rayleign-type waves; Love-type waves; Wave dispersion